Multigene expression in stable CHO cell pools generated with the piggyBac transposon system. (13th July 2016) - Balasubramanian, Sowmya; Wurm, Florian M.; Hacker, David L.
Abstract : Heterogenous populations of recombinant cells (cell pools) stably expressing 1–4 transgenes were generated from Chinese hamster overy (CHO) cells with the piggyBac (PB) transposon system. The cell pools produced different combinations of three model proteins—enhanced green fluorescent protein (EGFP), secreted alkaline phosphatase (SEAP), and a monoclonal IgG1 antibody. Each transgene was present on a separate PB donor plasmid with either the same or a different selection gene. In both cases, we obtained PB‐derived cell pools with higher recombinant protein yields than from cell pools generated by conventional gene delivery. In PB‐derived cell pools generated using a single selection agent, both protein production and the number of integrated copies of each transgene declined as the number of transfected transgenes increased. However, the total number of integrated transgenes was similar regardless of the number of different transgenes transfected. For PB‐derived cell pools generated by selection of each transgene with a different selection agent, the total number of integrated transgenes increased with the number of transfected transgenes. The results suggest that the generation of cell pools producing multiple recombinant proteins is feasible and that the method is more efficient when each individual transgene is selected with a different marker. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1308–1317, 2016